Influence of polymer coated aggregate on the aggregate impact and crushing value - A. F., Ahmad; A. R., Razali; F. R. M., Romlay; I. S. M., Razelan (IOP Publishing, 2021)
Polyethylene Terephthalate (PET) and latex belong to the family of the polymer. PET type of plastic bottle is the most commonly found in the household waste stream. Recycling this type of plastic into another form is the cheapest and the best way of recycling. However, this may not become a green waste management solution when energy is used to transform this plastic into another useable form. In this study, PET was used to discover the potential for improvement of asphalt mixture properties. This study examines the plastic waste used as an aggregate coating. PET plastic bottle was shredded and sieved to obtain size 0.425 to 0.075mm then was blended with hot aggregate to form a thin layer of plastic coating on the aggregate surface. The comparison between unmodified aggregate properties and modified properties was studied. 1%, 3%, 5%, 7%, 9%, 11%, 13% and 15% of plastic by weight of aggregate were used as aggregate coating. The aggregate impact value test (AIV) and aggregate crushing value test (ACV) were done on the plastic coated aggregate. The test result had shown an improvement in the properties of plastic coated aggregate. From the experiment results conducted on the PET and aggregate, we can conclude that the lowest percent of aggregate loss on the crushing value test is 16.34% when PET content is 9% while 8.00% when PET content is 13% for the impact value test. The lowest percent of aggregate loss for impact value is then compared with the percent loss of PET Latex coated aggregate. The presence of latex and PET has caused the strength of the aggregate to increase where the percentage loss value when performed impact test is very low that is can achieve 3.48%. The quality of flexible pavement can be improved when the surface of the aggregate is coated with the polymer.